2005
DOI: 10.1007/bf03324626
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in pressure pain threshold, grip strength and touch pressure threshold in upper extremities of older adults

Abstract: Despite the fact that age-related sensorimotor changes are not statistically significant, a reduction is seen in sensorimotor parameters after the age of 60.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Our age-related score distribution is consistent with previous literature from more detailed laboratory measures (Bleyenheuft et al, 2006;Donat, Ozcan, Ozdirenç, Aksakoglu, & Aydinoglu, 2005), suggesting that our brief functional measures reflect basic somatosensory processing.…”
Section: Patterns Of Somatosensory Perception Across the Lifespansupporting
confidence: 87%
“…Our age-related score distribution is consistent with previous literature from more detailed laboratory measures (Bleyenheuft et al, 2006;Donat, Ozcan, Ozdirenç, Aksakoglu, & Aydinoglu, 2005), suggesting that our brief functional measures reflect basic somatosensory processing.…”
Section: Patterns Of Somatosensory Perception Across the Lifespansupporting
confidence: 87%
“…On the other hand, an age-related grip strength reduction is shown in the elderly, although this reduction does not reach a statistical significant difference by aged distribution in this population (Donat et al, 2005). Moreover, Abizanda et al (2012) reported that the grip strength values were almost double in men than in women older adults.…”
Section: Introductionmentioning
confidence: 73%
“…This is reliable, reproducible and sensitive for latent MTrPs evaluation in older adults’ upper limbs (Donat et al, 2005; Neziri et al, 2011; Lautenbacher et al, 2005; Koo, Guo & Brown, 2013; Fisher, 1998; Park et al, 2011). The most hyperalgesic latent MTrP in the anterior deltoid and the most hyperalgesic latent MTrP in the ECRB ipsilateral to the painful shoulder (for the case group) or bilateral for the non-painful shoulders (for the control group) were assessed.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations